Wide metabolite coverage LC-MS/MS assay for the diagnosis of inherited metabolic disorders in urine - Ivanovová, Eliška; Piskláková, Barbora; Dobešová, Dana; Janečková, Hana; Foltenová, Hana; Kvasnička, Aleš; Prídavok, Matúš; Bouchalová, Kateřina; de Sousa, Julie; Friedecký, David (Talanta, 2024)
OBJECTIVE: The laboratory diagnosis of inherited metabolic disorders (IMD) has undergone significant development in recent decades, mainly due to the use of mass spectrometry, which allows rapid multicomponent analysis of a wide range of metabolites. Combined with advanced software tools, the diagnosis becomes more efficient as a benefit for both physicians and patients. METHODS: A hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry assay for determination of urinary purines, pyrimidines, N-acylglycines, N-acetylated amino acids, sugars, sugar alcohols and other diagnostically important biomarkers was developed and validated. Evaluation of the results consisting of utilisation of robust scaling and advanced visualization tools is simple and even suitable for urgent requirements. RESULTS: The developed method, covering 65 biomarkers, provides a comprehensive diagnostic platform for 51 IMD. For most analytes, linearity with R2 > 0.99, intra and inter-day accuracy between 80 and 120 % and precision lower than 20 % were achieved. Diagnostic workflow was evaluated on 47 patients and External Quality Assurance samples involving a total of 24 different IMD. Over seven years, more than 2300 urine samples from patients suspected for IMD have been routinely analysed. CONCLUSIONS: This method offers the advantage of a broad coverage of intermediate metabolites of interest and therefore may be a potential alternative and simplification for clinical laboratories that use multiple methods for screening these markers.
Keywords: Hydrophilic interaction chromatography; Metabolic Diseases; metabolické nemoci; Diagnosis; Inherited metabolic disorders; lidé; Liquid Chromatography-Mass Spectrometry; Mass spectrometry; tandemová hmotnostní spektrometrie; biologické markery; Chromatography, Liquid; kapalinová chromatografie-hmotnostní spektrometrie; Biomarkers; chromatografie kapalinová; Liquid chromatography; Tandem Mass Spectrometry; Humans